Avaliando conhecimento em DST de graduandos em medicina segundo a taxonomia de bloom - Bórnea, Eloá Rondi; Gonçalves, Aguinaldo; Padovani, Carlos Roberto [UNESP] (Associação Brasileira de Educação Médica, 2014)
Throughout a medical degree and its students' gradual entry into an area of specialization, cognitive assessments are widely applied and used in order to analyze learning procedures. The instrument used is not however always compatible or effective in evaluating the topics studied. Apart from gauging the extent of medical students' knowledge of STIs, the aim of this study is to investigate the existence of preferential distributions with regard to gender. In this descriptive observational cross-sectional study, 25 multiple-choice tests were, formulated according to Bloom's typology, the degree of difficulty and STIs' thematic core. They were then applied to 68 sixth-year interns. Results registered preferential distribution (p < 0.001) with homogeneity of students in the direction of the most frequent alternative and a polarization of correct answers in the categories of Knowledge and Analysis. The findings are representative of the current medical education model, in which the transmission of information dominates a development and reconstruction of knowledge, leading to the search for new strategies in teaching and assessment.

Durante a graduação e o ingresso na especialidade, as avaliações cognitivas são amplamente aplicadas e utilizadas para analisar o aprendizado. Entretanto, nem sempre o instrumento empregado é compatível e suficiente para avaliar os tópicos aprendidos. O objetivo da presente investigação, além de apreender o grau de conhecimento que graduandos de Medicina detêm sobre DST, é investigar a existência de distribuições preferenciais a respeito segundo o gênero. Trata-se de um estudo observacional transversal descritivo de retroanálise. Foi adotada uma bateria de 25 testes de múltipla escolha formulados segundo a tipologia de Bloom, grau de dificuldade, núcleo temático das DST e aplicados a 68 internos do sexto ano. Os resultados registraram distribuição preferencial (p < 0,001) com homogeneidade do alunado em direção à alternativa mais frequente e polarização dos acertos nas categorias Conhecimento e Análise. Esses dados ilustram o modelo de educação médica atual, em que predomina a transmissão de informações ao invés da elaboração e reconstrução do conhecimento, o que tem levado à busca de novas estratégias de ensino e avaliação.
Evaluating medical students' knowledge on STI according to bloom's taxonomy
Keywords: Educação Médica; Doenças Sexualmente Transmissíveis; Estudantes de Medicina; Avaliação Educacional; Medical Education; Sexually Transmitted Infections; Medical Students; Educational Assessment